1998
DOI: 10.1007/s002470050497
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence of intussusception in children: a 17-year review

Abstract: Rates and patterns of recurrence did not change with altered management. Because of the high reduction rate of recurrences, lack of perforation and favourable long-term follow-up, we recommend radiological reduction for recurrent INT. Multiple recurrences are not a contraindication. A careful search for PLP is mandatory. Surgery should be reserved for irreducible recurrences or for demonstrated PLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
89
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 12 publications
8
89
1
4
Order By: Relevance
“…Niramis et al [1] found that the success rates after BE and AE reduction in recurrent cases were as high as 96% and 92%, respectively. Reducibility was 95% for recurrent episodes in the series of Daneman et al [5]. In our study hydrostatic enema was effective in 100% of cases.…”
Section: Discussionsupporting
confidence: 50%
“…Niramis et al [1] found that the success rates after BE and AE reduction in recurrent cases were as high as 96% and 92%, respectively. Reducibility was 95% for recurrent episodes in the series of Daneman et al [5]. In our study hydrostatic enema was effective in 100% of cases.…”
Section: Discussionsupporting
confidence: 50%
“…Timing of intussusception recurrence can range from hours to years, and reliable predictors of recurrence have not been identified. 5,10,11 The management of recurrent intussusception has been repeat enema reduction with excellent outcome, even after multiple recurrences. It remains a challenge to identify patients at high risk for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Özellikle çoklu nükslerde bu ihtimal daha fazladır. [6,7,14] Tander ve ark. [6] üç yaş üzeri hastalarda hidrostatik redüksiyonun başarı oranı düşük olsa bile denenebileceğini, ancak hastanın klinik ve radyolojik olarak iyi bir gözlem altında tutulması gerektiğini belirtmektedirler.…”
Section: Discussionunclassified